2006
DOI: 10.1017/s0022215106001952
|View full text |Cite
|
Sign up to set email alerts
|

Role of mitomycin C in reducing adhesion formation following endoscopic sinus surgery

Abstract: Mitomycin C may be topically applied in post-operative FESS cases to reduce adhesion formation and hence the need for revision surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 11 publications
0
22
1
Order By: Relevance
“…These 46 consisted of 11 case reports [1020], 9 case series [2129], 7 prospective clinical trials [3, 3035], 5 RCTs [36–40], 2 reviews [41, 42], 12 animal studies [4, 5, 4352]. The first article about the topical use of MMC in the upper aerodigestive tract dates from 1998 [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These 46 consisted of 11 case reports [1020], 9 case series [2129], 7 prospective clinical trials [3, 3035], 5 RCTs [36–40], 2 reviews [41, 42], 12 animal studies [4, 5, 4352]. The first article about the topical use of MMC in the upper aerodigestive tract dates from 1998 [19].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies report adhesions and discharge at the MMC treated side, but these appeared significantly less frequently than on a similar wound treated with saline solution [30]. It is a principal point of discussion whether these effects can be seen as a result of the surgery proper and are in that notion not mentioned as being a side effect of topical MMC application.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier animal studies by Ingrams et al [11] reported a delay in Wbrosis which allowed re-epithelialization to take place before scar tissue forms, thus increasing the success rate of FESS. Clinical work done by Chung et al [12], Gupta and Motwani [13], Konstantinidis et al [14] has shown a reduction in the incidence of synechiae with topical Mitomycin C. Gupta and Motwani [13] also reported an improvement in nasal obstruction in his patients who were treated with topical Mitomycin C. However, other authors have not found beneWt with topical Mitomycin C [15,16]. A recent review of literature by Karkos et al [17] suggested a favorable shortterm eVect of Mitomycin C, but no evidence regarding long-term prevention of re stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…The author had good experience of using MMC in reducing adhesion formation following endoscopic sinus surgery [9]. The concentration recommended for local application is 0.4mg/ml.…”
Section: Discussionmentioning
confidence: 99%